In the previous section, we saw the sum of squares of the first n natural numbers. In this section, we will see sum of cubes of the first n natural numbers.
C. 13 + 23 + 33 +. . . + n3
This sum can be calculated in 8 steps:
1. Consider the identity: (a+b)4 = a4+4a3b+6a2b2+4ab3+b4
[Recall that (a+b) can be raised to any power by using binomial theorem that we saw in the previous chapter]
Let us put a = k and b = -1. We get:
[k+(−1)]4=[k−1]4=k4 + 4×k3×−1 + 6×k2×(−1)2 + 4×k×(−1)3 + (−1)4=k4 − 4k3 + 6k2 − 4k + 1
2. Subtracting (k-1)4 from k4, we get:
k4 − (k−1)4=k4 − (k4 − 4k3 + 6k2 − 4k + 1)=k4 − k4 + 4k3 − 6k2 + 4k − 1=4k3 − 6k2 + 4k − 1
• We can use this as an identity:
k4 − (k−1)4 = 4k3 − 6k2 + 4k − 1
3. In the above identity, let us put k = 1, 2, 3, . . . , n successively. We get:
When k = 1,14 − (1−1)4=14 − 04=4×13 − 6×12 + 4×1 − 1=4(1)3 − 6(1)2 + 4(1) − 1When k = 2,24 − (2−1)4=24 − 14=4×23 − 6×22 + 4×2 − 1=4(2)3 − 6(2)2 + 4(2) − 1When k = 3,34 − (3−1)4=34 − 24=4×33 − 6×32 + 4×3 − 1=4(3)3 − 6(3)2 + 4(3) − 1When k = 4,44 − (4−1)4=44 − 34=4×43 − 6×42 + 4×4 − 1=4(4)3 − 6(4)2 + 4(4) − 1−−−−−−−−−−When k = n,n4 − (n−1)4=4×n3 − 6×n2 + 4×n − 1=4(n)3 − 6(n)2 + 4(n) − 1
4. Picking the first and last items from each line, we get:
14 − 04=4(1)3 − 6(1)2 + 4(1) − 124 − 14=4(2)3 − 6(2)2 + 4(2) − 134 − 24=4(3)3 − 6(3)2 + 4(3) − 144 − 34=4(4)3 − 6(4)2 + 4(4) − 1−−−−n4 − (n−1)4=4(n)3 − 6(n)2 + 4(n) − 1
5. In the above result in (4), let us add all terms on the left side.
• We see that diagonal elements will get cancelled:
♦ 14 will get cancelled by -14.
♦ 24 will get cancelled by -24.
♦ 34 will get cancelled by -34.
♦ so on . . .
• So only 04 and n4 will remain.
• Thus the sum of all terms on the left side is: (n4 - 04) = n4.
6. In the result in (4), let us add all terms on the right side. We get:
4(13 + 23 + 33 +. . . + n3) - 6(12 + 22 + 32 +. . . + n2) + 4(1 + 2 + 3 +. . . + n) - (1+1+1+ . . . n times)
• This can be written in a shortened form using sigma notations:
4k=n∑k=0k3 − 6k=n∑k=0k2 + 4k=n∑k=0k − n
7. Equating the results in (5) and (6), we get:
n4=4k=n∑k=0k3 − 6k=n∑k=0k2 + 4k=n∑k=0k − n⇒4k=n∑k=0k3=n4 + 6k=n∑k=0k2 − 4k=n∑k=0k + n- - - - (a)⇒4k=n∑k=0k3=n4 + [6n(2n+1)(n+1)6] − 4k=n∑k=0k + n- - - - (b)⇒4k=n∑k=0k3=n4 + [6n(2n+1)(n+1)6] − [4n(n+1)2] + n⇒4k=n∑k=0k3=n4 + n(2n+1)(n+1) − 2n(n+1) + n⇒4k=n∑k=0k3=n4 + 2n3+2n2+n2+n − 2n2−2n + n⇒4k=n∑k=0k3=n4+2n3+n2⇒4k=n∑k=0k3=n2(n2+2n+1)- - - - (c)⇒4k=n∑k=0k3=n2(n+1)2⇒k=n∑k=0k3=n2(n+1)24⇒k=n∑k=0k3=[n(n+1)2]2
Remarks:
(i) The line marked as (a):
• k=n∑k=0k2 is in fact the sum of squares of first n natural numbers.
• So our second result B that we saw in the previous section can be used.
(ii) The line marked as (b):
• k=n∑k=0k is in fact the sum of first n natural numbers.
• So our first result A that we saw in the previous section can be used.
(iii) The line marked as (c):
• Using the identity (a+b)2 = a2 + 2ab + b2,
(n2 + 2n + 1) is (n+1)2
8. We can write the result as a formula:
Sum of cubes of the first n natural numbers
= 13 + 23 + 33 +. . . + n3
= k=n∑k=1k3 = [n(n+1)2]2
Let us see some solved examples:
Solved example 9.19
Find the sum to n terms of the series: 5 + 11 + 19 + 29 + 41 + . . .
Solution:
1. Let us write:
Sn = 5 + 11 + 19 + 29 + 41 + . . . + an−1 + an
2. The same result can be written as:
Sn = 5 + 11 + 19 + 29 + 41 + . . . + an−2 + an−1 + an
3. We will write the second result just below the first result. But one term to the right. We get:
Sn=5 + 11 + 19 + 29 + . . . + an−1 + anSn=5 + 11 + 19 + . . . + an−2 + an−1 + an
4. Subtracting each term in the second row, from the term directly above it, we get:
Sn=5 + 11 + 19 + 29 + . . . + an−1 + anSn=5 + 11 + 19 + . . . + an−2 + an−1 + an0=5 + {6 + 8 + 10 + . . . } − an
5. In the above result, there will be (n-1) terms inside the curly brackets '{}'
• In side the curly brackets, we have the series: 6 + 8 + 10 + . . . (n-1) terms
• It is an A.P with a = 6, d = 2 and n = (n-1)
• So sum of the series = (n−1)2[2×6+(n−1−1)2] = (n−1)2[12+(n−2)2] = (n−1)(6+n−2) = (n−1)(4+n)
6. Now the result in (4) becomes:
0 = 5 + (n-1)(4+n) - an
⇒ an = 5 + (n-1)(4+n)
⇒ an = 5 + 4n + n2 - 4 - n
⇒ an = 1 + 3n + n2
⇒ an = n2 + 3n + 1
7. Thus we obtained the nth term.
• nth term = an = n2 + 3n + 1.
• So the sum (Sn) of the given series can be obtained as:
Sn=k=n∑k=0ak = k=n∑k=0(k2+3k+1)=k=n∑k=0k2 + 3k=n∑k=0k + n- - - - (a)=n(2n+1)(n+1)6 + 3k=n∑k=0k + n- - - - (b)=n(2n+1)(n+1)6 + 3n(n+1)2 + n=n(2n+1)(n+1) + 9n(n+1) + 6n6=n[(2n+1)(n+1)+9(n+1)+6]6=n[2n2+2n+n+1+9n+9+6]6=n[2n2+12n+16]6=2n[n2+6n+8]6=n[n2+6n+8]3- - - - (c)=n[(n+2)(n+4)]3
Remarks:
(i) The line marked as (a):
• k=n∑k=0k2 is in fact the sum of squares of first n natural numbers.
• So our second result B that we saw in the previous section can be used.
(ii) The line marked as (b):
• k=n∑k=0k is in fact the sum of first n natural numbers.
• So our first result A that we saw in the previous section can be used.
(iii) The line marked as (c):
• n2 + 6n + 8 = 0 can be solved as a quadratic equation.
• We will get: n = -2 and n = -4.
Solved example 9.20
Find the sum to n terms of the series whose nth term is n(n+3)
Solution:
• nth term = n(n+3).
• So the sum (Sn) of the given series can be obtained as:
Sn=k=n∑k=0[k(k+3)] = k=n∑k=0[k2+3k]=k=n∑k=0k2 + 3k=n∑k=0k- - - - (a)=n(2n+1)(n+1)6 + 3k=n∑k=0k- - - - (b)=n(2n+1)(n+1)6 + 3n(n+1)2=n(2n+1)(n+1) + 9n(n+1)6=n[(2n+1)(n+1)+9(n+1)]6=n[2n2+2n+n+1+9n+9]6=n[2n2+12n+10]6=2n[n2+6n+5]6=n[n2+6n+5]3- - - - (c)=n[(n+1)(n+5)]3
Remarks:
(i) The line marked as (a):
• k=n∑k=0k2 is in fact the sum of squares of first n natural numbers.
• So our second result B that we saw in the previous section can be used.
(ii) The line marked as (b):
• k=n∑k=0k is in fact the sum of first n natural numbers.
• So our first result A that we saw in the previous section can be used.
(iii) The line marked as (c):
• n2 + 6n + 5 = 0 can be solved as a quadratic equation.
• We will get: n = -1 and n = -5.
The link below gives some more solved examples
In the next section we will see some miscellaneous examples.